Nodular Cutaneous Amyloidosis at the Temple - Kathrin Schucht; Josef Schröder; Heiko Siegmund; Claudia Grafe; Stephan Schreml (Karger Publishers, 2016)
A 52-year-old woman presented with a large partially yellow and erythematous tumor on her right temple. She reported that it had grown over the last 4 years. Regional lymph nodes were impalpable. A punch biopsy showed eosinophilic material in the dermis and subcutis. Immunohistochemistry showed positive staining for kappa and lambda light chains. Electron microscopy showed the typical amyloid fibrils (7-10 nm in diameter). There was no evidence of systemic amyloidosis, paraproteinemia or underlying plasmacytoma. The tumor was completely removed via curettage. At follow-up, the patient presented in good health with no signs of relapse.